The Effect of the University Library on Students in the Accounting Program's Academic Success - Vinny Stephanie Hidayat; Aurora Angela; Cristian Jovi (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
The purpose of this study is to see how the University Library affects auditing students. The participants in this study are all of Maranatha Christian University's Auditing students. This study's sample consists of auditing students (students of 2015-2020). Explanatory research was used in this study, and purposive sampling was used as the sample strategy. For research hypothesis testing, SPSS version 20.0 is used. T tests, F tests, and multiple regression analysis are used. The findings of this study suggest that the University Library has an impact on a student's academic success